Updating the occurrences of Pterois miles in the Mediterranean Sea, with considerations on thermal boundaries and future range expansion - DIMITRIADIS, CHARALAMPOS; GALANIDI, MARIKA; ZENETOS, ARGYRO; CORSINI-FOKA, MARIA; GIOVOS, IOANNIS; KARACHLE, PARASKEVI K.; FOURNARI – KONSTANTINIDOY, IVONI; KYTINOU, ELENI; ISSARIS, YIANNIS; AZZURRO, ERNESTO; CASTRIOTA, LUCA; FALAUTANO, MANUELA; et al. (Mediterranean marine science, 2020)
Here we present an update of the Mediterranean distribution of the lionfish Pterois miles, based on a comprehensive list of geo-referenced occurrences up to October 2019. New data were provided by multiple reporting tools and citizen science initiatives. Our findings suggest that well established populations of P. miles exist in the Levantine Sea, in the southern and central Aegean Sea, as well as in the Greek Ionian Sea, whilst so far, only a few individuals were reported from Tunisia and southern Sicily (Italy). We also argue about the future expansion of this invasive species in the Mediterranean region and about the role of climate change by projecting the limits of winter isotherms under different climate change scenarios. Under the assumption that the mean winter sea surface temperature is the main limiting factor of the range expansion of the species (i.e. 15.3oC winter isotherm), P. miles could substantially expand in the Mediterranean Sea, except the coolest northernmost regions, under future climatic scenarios. These results were discussed in comparison to published outcomes of species distribution modelling.